Astrocyte proliferation in the hippocampal dentate gyrus is suppressed across the lifespan of dystrophin‐deficient mdx mice - Kimberley A. Stephenson; Polly Peters; Mark G. Rae; Dervla O'Malley (Experimental Physiology)
Abstract Absence of the structural protein, dystrophin, results in the neuromuscular disorder Duchenne Muscular Dystrophy (DMD). In addition to progressive skeletal muscle dysfunction, this multisystemic disorder can also result in cognitive deficits and behavioural changes that are likely to be consequences of dystrophin loss from central neurons and astrocytes. Dystrophin‐deficient mdx mice exhibit decreases in grey matter volume in the hippocampus, the brain region that encodes and consolidates memories, and this is exacerbated with ageing. To understand changes in cellular composition that might underpin these age‐related developments, we have compared neurogenesis and the prevalence of immunofluorescently identified newly born and mature neurons, astrocytes and microglia in the dentate gyrus of mdx and wild‐type mice at 2, 4, 8 and 16 months of age. The number of adult‐born neurons was suppressed in the dentate gyrus subgranular zone of 2‐month‐old mdx mice. However, the numbers of granule cells and GABAA receptor, alpha 1‐expressing cells were similar in wild‐type and mdx mice at all ages. Strikingly, the numbers of astrocytes, particularly in the dentate gyrus molecular layer, were suppressed in mdx mice at all time points. Thus, dystrophin loss was associated with reduced hippocampal neurogenesis in early life but did not impact the prevalence of mature neurons across the lifespan of mdx mice. In contrast, normal age‐related dentate gyrus astrocyte proliferation was suppressed in dystrophic mice. Astrocytes are the most abundant cell type in the brain and are crucial in supporting neuronal function, such that loss of these cells is likely to contribute to hippocampal dysfunction reported in mdx mice.